Unequal translingual Englishes in the asian peripheries - Dovchin, Sender; Sultana, S.; Pennycook, A. (ALC Press, 2016)
© 2016 Informa UK Limited, trading as Taylor & Francis Group This article seeks to expand the current discussions on the notion of ‘translingual Englishes’ by incorporating the idea of ‘unequal Englishes’ as a way of understanding the role of English in relation to understudied Asian peripheral contexts such as Mongolia and Bangladesh. It is clear that young speakers in these Asian countries are creatively involved with ‘translingual Englishes’, in which various English and other linguistic and cultural resources are in constant interplay. Yet there are also particular local constraints that either limit or expand their usage of English. Translingual Englishes may be creative and playful but they are also associated with differences in one’s unequal social class, wealth and power.